SWOT Analysis of Afghanistan’s Coal Trade in International Market - Aslami, Alyas (International Journal of Multidisciplinary Approach Research and Science, 2025)
This study examines the SWOT analysis of Afghanistan’s coal trade in the international market. The analysis highlights the strengths, weaknesses, opportunities, and threats. Afghanistan has huge amount of coal reserves about 73 million tons that can be exploited for exports to international market. Also, this paper identifies the ways to growth of Afghan coal trade in the international market. There are several issues in the Afghan coal trade in the international market for addressing. Afghanistan has several opportunities for growth of coal trade that should be capitalized, such as coal demand increasing and development of infrastructure. There are several threats that should be mitigated, such as environmental concerns. Also, this paper identifies Afghanistan position in the international market of coal trade. Afghanistan has moderate position in the international market of coal trade. Currently, Afghanistan has exports of coal to Pakistan. The amount of coal trade to Pakistan was 2.7 million tons in 2022 with 12 billion and 143 million AFG revenue.